International multidisciplinary team discussions on the diagnosis of idiopathic non-specific interstitial pneumonia and the development of connective tissue disease. Issue 1 (1st January 2021) - Møller, Janne; Altraja, Alan; Sjåheim, Tone; Rasmussen, Finn; Madsen, Line Bille; Bendstrup, Elisabeth
ABSTRACT: Background: Idiopathic Non-Specific Interstitial Pneumonia (iNSIP) is a rare interstitial lung disease, diagnosed, by definition, on the basis of a multidisciplinary team discussion (MDD). Association with an autoimmune background has been suggested in iNSIP. Aims: To test the feasibility of conducting a multinational MDD to review the diagnosis in iNSIP cases and to estimate the emergence of connective tissue disease (CTD) during follow-up. Methods: Investigators from three expert centers (Denmark, Estonia and Norway) met and discussed cases of biopsy-proven iNSIP at an international MDD. The cases were previously diagnosed at a national level between 2004 and 2014. Based on clinical, radiographic and pathological data, the diagnosis of iNSIP was re-evaluated and a consensus diagnosis was made. Cases incompatible with iNSIP were excluded. Relevant data were registered comprising any development of CTD. Results: In total, 31 cases were discussed and 23 patients were included with a diagnosis of iNSIP. The mean follow-up time was 57 months. None of the patients developed CTD according to the rheumatologic criteria during the follow up period. Four patients (17.4%) met the criteria for interstitial pneumonia with autoimmune features. Conclusion: We found that an international MDD was a feasible and valuable tool in the retrospective diagnostic evaluation of iNSIP. Diagnosis was changed in a statistically significant number of patients by our international MDD team. None of the patients developed CTD during follow-up.